Features of the Emotional Sphere of the Personality of Urban Medical Students in the Educational Process - Kira G. Serdakova; Valeria I. Shelest; Natalya A. Krylova; Olga V. Smirnikova; Ilya I. Khersonsky; Valeria F. Shubina (National Research Mordova State University, 2023)
Introduction. The emotional sphere of a personality is shaped under the influence of the system of public relations, which has its own specifics in the universities of the metropolis. Modern conditions have a limited amount of data on the development of the emotional and personal sphere and the possible risks of socio-psychological maladaptation of medical students studying in a megalopolis. For the first time, the emotional sphere of personality is considered in the context of manifestation of possible social maladaptation (conflict, stress, anxiety, neuroticism) of medical students in the conditions of the educational process in the megapolis. The aim of our work was to look into the emotional sphere of the personality of urban medical students in the conditions of the educational process drawing on their conflict, anxiety, neuroticism. Materials and Methods. 105 medical students of various years of studies, living and studying in the megapolis, took part in the survey. A set of diagnostic techniques was used. The cross-sectional method was used to collect data. The results were processed using the SPSS program. Results. Significant differences in the assessments of neuroticism among students of different years were found. There was a significant difference in stress assessments between first and last year students. The results differ significantly among students from different clusters based on cluster analysis of stress, anxiety and neuroticism assessments. The assessment of anxiety, stress and neuroticism makes it possible to talk about certain types of students in the context of maladaptation: type 1 - adapted, type 2 - have risks of development of maladaptation, type 3 - prone to maladaptation. It was also noted that the conflict of girls is expressed higher than the conflict of boys. Discussion and Conclusion. The conclusions made by the authors contribute to the development of psychological and pedagogical knowledge that improves the training systems in a medical university. The materials of the article can be useful for teachers and administrators when interacting with students of all years of study. The assumption of a combination of all social maladaptation on a certain year of study is refuted, which indicates the need to continue the study.